The relationship between attitude, intention and behavior towards mobile advertising amongst undergraduate students - Abu Seman, Noor Aslinda (EduPedia Publictions, 2018)
The quick technology development in the realm of smartphones has made another medium for marketing of most companies. The utilization of smartphone as a promoting instrument to achieve customers around the global is presently progressively well known, making the smartphone as a perfect medium to reach buyers independently. This empirical study aims to examine the attitudes and behavior of students towards mobile advertising that conducted by marketers. The purpose of this empirical study is to recognize the contributing elements in the advertisement messages which can influence the attitudes toward the advertisement received, and examine the relationship between attitude, intention and behavior of students toward mobile advertising. A total of 100 participants conducted in this study using the convenience sampling method. The results demonstrated consumers for the most part have negative attitudes towards mobile advertising except if they have authorization to get it. The findings also found that entertainment factor positively can improve consumer attitudes. This empirical study also confirmed there is a direct relationship between consumer attitudes and consumer intention, and relationship between consumer intention and consumer behavior. Along these lines, by identifying the elements outlined, this present study may help companies to improve their advertising quality, make strategic planning and identify potential new opportunities emerging in addition to being the most effective company in mobile advertising.